2013
DOI: 10.1242/jcs.124586
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a triosephosphate isomerase non-catalytic function critical to behavior and longevity

Abstract: SummaryTriosephosphate isomerase (TPI) is a glycolytic enzyme that converts dihydroxyacetone phosphate (DHAP) into glyceraldehyde 3-phosphate (GAP). Glycolytic enzyme dysfunction leads to metabolic diseases collectively known as glycolytic enzymopathies. Of these enzymopathies, TPI deficiency is unique in the severity of neurological symptoms. The Drosophila sugarkill mutant closely models TPI deficiency and encodes a protein prematurely degraded by the proteasome. This led us to question whether enzyme cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…TPI Deficiency is unique among all other glycolytic enzymopathies in the presentation of severe neurologic deficits and the lack of ATP depletion [2]. It is not currently understood why mutations in a non-linear glycolytic enzyme elicit far greater pathology than other central glycolytic enzymes, though recent work has suggested that these neurologic differentiae are derived from a source other than general metabolic stress [3]. To date, only one of eleven physically distinct disease-associated TPI mutations has been structurally characterized [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…TPI Deficiency is unique among all other glycolytic enzymopathies in the presentation of severe neurologic deficits and the lack of ATP depletion [2]. It is not currently understood why mutations in a non-linear glycolytic enzyme elicit far greater pathology than other central glycolytic enzymes, though recent work has suggested that these neurologic differentiae are derived from a source other than general metabolic stress [3]. To date, only one of eleven physically distinct disease-associated TPI mutations has been structurally characterized [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…diet, environment, quality of medical care), play a role in the development of this enigmatic disease. Indeed data from a Drosophila study has indicated the existence of an isomerase-independent function of TPI which opens up new avenues of investigation that may prove crucial in developing our understanding of this enzyme in the conservation of normal neuronal function and, therefore, in TPI deficiency pathogenesis (Roland et al, 2015;Roland et al, 2013). Other non-metabolic functions of TPI have also been reported in a number of organisms, mostly pathogens.…”
Section: Protein Stability Is An Important Factor In Predicting Diseamentioning
confidence: 98%
“…Structural studies were based on the crystal structure of human TPI (PDB: 4POC; (Roland et al, 2015;Roland et al, 2013)) obtained from the RCSB protein data bank (http://www.rcsb.org/pdb/home/home.do) (Berman et al, 2002;Berman et al, 2000). Secondary structural elements were defined according to Supplementary Table S2.…”
Section: Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of enzymatic activity most likely results from misfolding of the enzyme or its failure to dimerize (Daar et al 1986;Seigle et al 2008 andRalser et al 2006). Furthermore, the TIM knockout can lead to metabolic diseases and neurological dysfunction (Velur Selvamani et al 2014;Roland et al 2013;Eanes et al 2006) Giardia depends on glycolysis as its major ATP source (Adam 2001). TIM from Schistosoma species was considered as a potential drug and vaccine target Wen 2011 andZinsser et al 2013a, b).…”
Section: Introductionmentioning
confidence: 99%